Memorandum of understanding between Universiti Teknologi MARA and Persatuan Biblioterapi Malaysia / Fakulti Pengurusan Maklumat - Universiti Teknologi MARA, Fakulti Pengurusan Maklumat (Universiti Teknologi MARA (UiTM), 2021)
UiTM and Persatuan Biblioterapi Malaysia will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.